Desenvolvimento de iogurte adicionado de geleia de pétalas de rosas: perspectivas sensorial e estudo de consumidores - Cielo, Daiane Palma (2018)
Consumers have become increasingly aware of food, and that it is intertwined with a healthy and balanced lifestyle. The search for a nutritionally balanced diet has the objective of maintaining health and preventing diseases, this has caused a greater interest by the population, occurring to the search for foods that provide health promoting effects through their benefits. Yogurt is one of the fermented dairy products that have great economic relevance for Brazil, as well as being a world-popular product and possessing great nutritional value. In this context, the present work aimed at the development of protein yogurt added with rose petal jelly. Initially we investigated the sensorial perception of Brazilian consumers about edible flowers, information and the attitude of the two conditions, in which the expressions inducing for the words free association terms were: a "food made with flowers" and "yoghurt made with flowers ". To achieve this goal, terms of free association of words were applied. A total of 549 consumers participated in this study. Subsequently, yogurts were elaborated with two different concentrations of whey protein: 10% being identified as Treatment 1 (T1) and 12% Treatment 2 (T2) for each 100 mL of milk, being these compared to the Control Treatment (T3) developed without addition of whey protein. In the three formulations developed the microbiological quality was analyzed, being also characterized physico-chemically and carried out the shelf-life monitoring during 28 days of storage. Total acidity, pH, protein content and color were analyzed. The check-all-that-aplly (CATA) method was applied in order to seek a direct link with consumers. The results showed a positive attitude towards both situations, and consumers associated flower-based food products with "health care," while the central core of yoghurt made with flowers reflected the innovative condition of this product. Microbiological analyzes indicated the absence of total coliforms, thermotolerantes, molds and yeasts and Salmonella sp. during the 28 days of storage. During the storage period, it was observed, as expected, an increase in total acidity and a decrease in the pH value for all yogurts. The results of the analysis of the protein content of the treatments T1 and T2, were around 13% and 14%, respectively, both of which can be considered protein source foods. In the sensorial aspect, the addition of whey protein impaired the texture of the developed yoghurts, because the higher the concentration, the more consistent and lumpy the product. The T3 treatment, which did not have whey protein, was the one that presented better performance in the queries of the sensorial descriptors.